Beth Levine in memoriam - An, Zhenyi (2020)
Beth Levine was born on 7 April 1960 in Newark, New Jersey. She went to college at Brown University where she received an A.B. Magna Cum Laude, and she attended medical school at Cornell University Medical College, receiving her MD in 1986. She completed her internship and residency in Internal Medicine at Mount Sinai Hospital in New York, and her fellowship in Infectious Diseases at The Johns Hopkins Hospital. Most recently, Beth was a Professor of Internal Medicine and Microbiology, Director of the Center for Autophagy Research, and holder of the Charles Sprague Distinguished Chair in Biomedical Science at the University of Texas Southwestern Medical Center in Dallas. Beth died on 15 June 2020 from cancer. Beth is survived by her husband, Milton Packer, and their two children, Rachel (26 years old) and Ben (25 years old). Dr. Levine was as an international leader in the field of autophagy research. Her laboratory identified the mammalian autophagy gene BECN1/beclin 1; identified conserved mechanisms underlying the regulation of autophagy (e.g. BCL2-BECN1 complex formation, insulin-like signaling, EGFR, ERBB2/HER2 and AKT1-mediated BECN1 phosphosphorylation); and provided the first evidence that autophagy genes are important in antiviral host defense, tumor suppression, lifespan extension, apoptotic corpse clearance, metazoan development, Na,K-ATPase-regulated cell death, and the beneficial metabolic effects of exercise. She developed a potent autophagy-inducing cell permeable peptide, Tat-beclin 1, which has potential therapeutic applications in a range of diseases. She was a founding Associate Editor of the journal Autophagy and an editorial board member of Cell and Cell Host & Microbe. She has received numerous awards/honors in recognition of her scientific achievement, including: The American Cancer Society Junior Faculty Research Award (1994); election into the American Society of Clinical Investigation (2000); the Ellison Medical Foundation Senior Scholars Award in Global Infectious Diseases (2004); elected member, American Association of Physicians (2005); appointment as a Howard Hughes Medical Institute Investigator (2008); Edith and Peter O’Donnell Award in Medicine (2008); elected fellow, American Association for the Advancement of Science (2012); election into the National Academy of Sciences (2013); election into the Academy of Medicine, Engineering and Science of Texas (2013); the ASCI Stanley J. Korsmeyer Award (2014); Phyllis T. Bodel Women in Medicine Award, Yale University School of Medicine (2018); recipient, Barcroft Medal, Queen’s University Belfast (2018).